Integrated Exposure and Algal Ecotoxicological Assessments of Effluents from Secondary and Advanced‐Tertiary Wastewater‐Treatment Plants. (24th August 2022) - Palumbo, Maria Teresa; Russo, Simona; Polesello, Stefano; Guzzella, Licia; Roscioli, Claudio; Marziali, Laura; Valsecchi, Lucia; Cappelli, Francesca; Pascariello, Simona; Tasselli, Stefano; Villa, Sara; Peruzzo, Massimo; et al.
Abstract: The great concern over the environmental impact of wastewaters has led to the designing of advanced treatment processes to upgrade conventional treatment plants and achieve a significant reduction of contaminants in receiving waters. In the present study we combined chemical and ecotoxicological analyses, aiming to evaluate the reduction of toxicity effects associated with the removal of micropollutants and to define the contribution of the detected compounds to the overall toxicity of the mixtures in a series of wastewater effluents collected from a secondary treatment (OUT 2) and from a tertiary activated carbon treatment (OUT 3) plant. The target compounds were selected after a screening procedure among pharmaceuticals, musk fragrances, and trace metals. The classical algal growth inhibition test was conducted on the original effluent samples and on different fractions obtained by solid‐phase extraction (SPE) treatment. A good accordance was found between the removal of toxicity (30%–80%) and organic compounds (70%–80%) after the tertiary treatment, suggesting its high efficiency to improve the wastewater quality. The discrepancy between the contribution to the overall toxicity of the nonadsorbable compounds (i.e., inorganic or very polar organic compounds) as experimentally measured by the SPE bioassays (18%–76%) and calculated by the concentration addition approach (>97%) could be mitigated by including the bioavailability correction in metal‐toxicity modeling of wastewater mixtures. For the organic compounds, the toxic equivalency method enabled us to quantify the portion of toxicity explained by the detected chemicals in both OUT 2 (82%–104%) and OUT 3 (5%–57%), validating the selection of the target molecules. The applied integrating approach could be implemented by the inclusion of both additional target chemicals and toxicity endpoints. Environ Toxicol Chem 2022;41:2404–2419. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.